Bottleneck Problems and Countermeasures in Operation and Maintenance of Non-Point Source Pollution Ecological Treatment Projects in China - Yungeng Jiang; Jing Zhang; Xiaoxin Liu; Han Liu; Yurui Ma; Wanhui Wang; Shaoyong Lu (Agronomy)
At present, non-point source pollution (NPSP) has overtaken point source as the most important source of water pollution in China. Ecological treatment projects (ETP) suitable for non-point source pollution have been widely recommended. However, China’s NPSP prevention system has not yet taken shape, the implementation and management levels are disorganized, and the long-term management and protection of NPSP-ETP remains an urgent problem. This paper focuses on the practical problems encountered in the promotion of ETP in China, and ways to solve these problems in the operation and maintenance process. First, problems encountered in the practice of NPSP-ETP in China are summarized as being caused by a lack of systematic regulation on operation and maintenance. Following this, promising countermeasures to solve these problems are proposed, including establishing an ecological treatment technology system, improving the technology selection assessment system, improving the assessment method in project operation, and establishing a systematic operation and maintenance process. Finally, a novel theory of Monitoring-Assessment-Repair (MAR) for ETP is proposed to solve the systematic bottlenecks in engineering operation and maintenance. Furthermore, the problem of clogging in infrastructure is discussed in detail, to illustrate the concrete operation of MAR theory. Overall, this study clarifies the issues in favor of a long-term mechanism of NPSP prevention in and beyond China.